A disputa entre Guyana e Suriname acerca das fronteiras marítimas (2000-2007) - Sousa, Yolanda Nunes (2019)
This paper aims to understand the origin and the main outlines of the dispute over the maritime borders between Guyana and Suriname, with special attention between the years 2000-2007. These two countries are in a geopolitical position of fusion and encounter between the Caribbean and the Amazon region, providing a rich field of research. The methodology adopted was twofold. The first one consisted of consulting the specialized bibliography, which would corroborate in order to draw a general picture of the region, that would bring elements of the social, political and economic profile of the countries in question and that would delimit questions specific to the Law of the Sea. The second way was through the analysis of official documents presented to the Arbitral Tribunal as well as the documents related to the decision of the case. The main considerations about the research point out that the bilateral relationship between Guyana and Suriname was built on the basis of pendular dynamics, that is, it now pointed to an approximation now to distance, in which attempts to define boundaries (especially the maritime border) have developed. Tables of tension, threat of force, low degree of effective integration, fragile bilateral relations, based on mistrust, which together reflected divergent claims regarding the delimitation of the maritime space. Such claims were arbitrated internationally whose decision, establishing a single maritime border, corroborates the gradual process of stability between the two countries.